2013
DOI: 10.1111/ddg.12011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of silicone gel on standardized postoperative scars

Abstract: The use of silicone gel caused subjective differences within the same scar (worsening as well as improvement of the appearance). Positive effects were not detectable in the investigated parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…In 2013, Riedel et al 17 published a study of 20 patients who underwent removal of a costal cartilage segment; half of the scar was treated with silicone gel for 3 months and the other half was used as a control. The scars were evaluated visually; of 19 patients, only 8 showed improvement, and 10 of 19 showed worsening on visual evaluation.…”
Section: Siliconementioning
confidence: 99%
See 1 more Smart Citation
“…In 2013, Riedel et al 17 published a study of 20 patients who underwent removal of a costal cartilage segment; half of the scar was treated with silicone gel for 3 months and the other half was used as a control. The scars were evaluated visually; of 19 patients, only 8 showed improvement, and 10 of 19 showed worsening on visual evaluation.…”
Section: Siliconementioning
confidence: 99%
“…Nevertheless, a majority of these studies have limitations: small sample size [7][8][9][13][14][15][16][48][49][50] , lack of objectivity in the evaluation criteria [10][11][12][13][14][15][16][48][49][50] , lack of control group 13,15,16 , and lack of standardization in the selection of patients 7,8 . Indeed, 2 studies concluded that silicone was not able to prevent hypertrophy in postoperative scars 17,51 . Niessen et al 51 stated that they started the treatment too early, 2 days after surgery, while still in the inflammatory phase.…”
Section: Siliconementioning
confidence: 99%